Biogeochemical and microbial seasonal dynamics between water column and sediment processes in a productive mountain lake: Georgetown Lake, MT, USA. Issue 8 (8th August 2016) - Parker, Stephen R.; West, Robert F.; Boyd, Eric S.; Feyhl‐Buska, Jayme; Gammons, Christopher H.; Johnston, Tyler B.; Williams, George P.; Poulson, Simon R.
Abstract: This manuscript details investigations of a productive, mountain freshwater lake and examines the dynamic relationship between the chemical and stable isotopes and microbial composition of lake bed sediments with the geochemistry of the lake water column. A multidisciplinary approach was used in order to better understand the lake water‐sediment interactions including quantification and sequencing of microbial 16S rRNA genes in a sediment core as well as stable isotope analysis of C, S, and N. One visit included the use of a pore water sampler to gain insight into the composition of dissolved solutes within the sediment matrix. Sediment cores showed a general decrease in total C with depth which included a decrease in the fraction of organic C combined with an increase in the fraction of inorganic C. One sediment core showed a maximum concentration of dissolved organic C, dissolved inorganic C, and dissolved methane in pore water at 4 cm depth which corresponded with a sharp increase in the abundance of 16S rRNA templates as a proxy for the microbial population size as well as the peak abundance of a sequence affiliated with a putative methanotroph. The isotopic separation between dissolved inorganic and dissolved organic carbon is consistent with largely aerobic microbial processes dominating the upper water column, while anaerobic microbial activity dominates the sediment bed. Using sediment core carbon concentrations, predictions were made regarding the breakdown and return of stored carbon per year from this temperate climate lake with as much as 1.3 Gg C yr −1 being released in the form of CO2 and CH4 . Key Points: Freshwater lake water column biogeochemistry and methane generation Shallow sediment biogeochemistry and microbiology Carbon turnover, stable isotopes, and seasonal methane flux